Ring-theoretic properties of augmented Iwasawa algebras - Timmins, J (2023)
Let p be a prime, G be a p-adic Lie group and k be a field of characteristic p. The augmented Iwasawa algebra kG is a noncommutative algebra extending the construction of the Iwasawa algebra of a compact p-adic Lie group. In this thesis we investigate the ring-theoretic properties of augmented Iwasawa algebras.